Principal component analysis of bodyweight and morphometric traits in Japanese Quail (Coturnix coturnix japonica) - Victoria O. Chimezie; Adeyinka Oye Akintunde; Abimbola Alice Ademola; F. A. Aina (Syiah Kuala University, 2022)
Principal component analyses were used to evaluate sexual dimorphism and the relationship among morphometric traits of Japanese quail (Coturnix coturnix japonica). A total of 153-day old quails (92 males and 61 females) were used in the study. The birds were housed in a wooden cage and fed ad-libitum. Data on body weight, body length, body girth, shank length, drumstick, wing length, keel length and shank length were obtained on a weekly basis using digital scale balance, measuring tape, and vernier caliper for a period of eight weeks. Principal component analysis was performed on the data obtained using the dimension reduction with factor analysis and morphometric traits were also correlated with body weight using SPSS statistical package version 21. Female birds had a significant higher (p0.05) body weight, body girth, drumstick, and wing length value than male counterpart, while no significant difference was observed for body length and shank diameter in both genders. A significant (p0.05) high and positive correlation coefficient was obtained between body weight and other linear measurements in both sexes. For both the male and female birds, one principal component was extracted, which explained 87.79 percent and 91.34 percent of the total variation observed in both species, respectively. . The principal components had its highest loading on keel length for both male and female Japanese quail and correlated highly with all parameters measured. Thus, the keel length could be used as selection criteria for improving body weight of Japanese quail.